2002
DOI: 10.1097/00000539-200202000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Intravenous Crystalloid Administration and Incidence of Cardiovascular Side Effects During Spinal Anesthesia: The Results from a Randomized Controlled Trial

Abstract: Crystalloids are frequently administered to nonobstetric patients minutes before spinal anesthesia to prevent cardiovascular side effects (CVSE). This randomized controlled trial shows that although crystalloids administered before spinal block result in no clinical benefit, they significantly reduce the risk of CVSE when administered at the time of spinal block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
0
23
0
3
Order By: Relevance
“…The reported rates of spinal anesthesia-induced hypotension in various studies range between 5% and 60%. This wide range is due to the description of hypotension, the time interval when blood pressure measurements are made, age, sex, type of operation, presence of hypertension or diabetes, and the techniques used to collect data (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported rates of spinal anesthesia-induced hypotension in various studies range between 5% and 60%. This wide range is due to the description of hypotension, the time interval when blood pressure measurements are made, age, sex, type of operation, presence of hypertension or diabetes, and the techniques used to collect data (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that increase the risk of hypotension include patient factors (advanced age, female sex, pregnancy, obesity, diabetes mellitus, hypertension, and anemia) and technical factors such as a block level at or above T5, use of opioids during premedication, and high local anesthetic dosages (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Mojica JL et al 8 have studied regarding the timing of IV fluids during spinal anaesthesia and found coloading (IV fluids during spinal anaesthesia) is more advantageous than preloading in prevention of severe hypotension or Arndlt JO et al 9 compared effectiveness of fluids and prophylactic vasopressors in prevention of severe hypotension. We used 15 mL/kg of Ringer's lactate to reason out hypotension was mainly the effect of vasodilatation after spinal and precipitated effect of antihypertensives and not due to absence of coloading.…”
Section: Discussionmentioning
confidence: 99%
“…Randomisiert-kontrollierte Studien zeigen keine eindeutigen Ergebnisse zu den Effekten der Inzidenz einer mütterlichen Hypotonie nach "Preloading/ Coloading" im Vergleich zu keinem Flüssigkeitsbolus während der SpA-Anlage [129][130][131][132][133][134][135]. Die Expertenkommission vermutet allerdings, dass durch "Preloading" eine Hypotension nach Anlage einer SpA reduziert werden kann, wobei keine Zeit durch diese Maßnah-me vergeudet werden sollte.…”
Section: V Flüssigkeitunclassified